Mediation services at the Family Courts of Singapore and Australia: Lessons for Malaysia - Mohd Arshad, Ain Husna; Che Soh @ Yusoff, Roslina; Mohd Zin, Najibah; Abdul Hak, Nora (2016)
Family mediation has become an important tool in resolving family disputes. Family courts all over the world have adopted mediation as part and parcel of their structure, or as a mandatory process in dispensing justice. The purpose of this paper is to learn how mediation is integrated into, or upheld by the family courts, particularly because of the need to develop a comprehensive and holistic family court system in Malaysia. In this paper, two family courts are studied i.e., the family courts in Singapore and in Australia. The discussion in this paper begins with a brief introduction on family mediation as practised in the Malaysian courts. This is followed by a discussion on the law and practise of mediation in the family courts of Singapore and Australia. The effectiveness of family mediation in these two countries is also discussed in general. It is found that mediation in family courts have been systematically and successfully implemented. It is also learned that mediation has been able to help the family courts to expedite the cases brought before the courts and clear backlogs. Even though there are certain differences in the way mediation is implemented in the family courts, it is proven that mediation is able to facilitate the parties to achieve a resolution, which is more satisfactory. In this paper, the data are obtained from materials consisting of textbooks, statutes, journal articles, newspapers, seminar and conference papers and unpublished writings. Interviews with the relevant personnel are also conducted. It is hoped that the findings of this study will be of help to the relevant authorities like the Malaysia Judiciary Department and Attorney General Department in designing a new regulatory framework in an effort to introduce mediation service at the proposed family court in Malaysia.